Evaluation of Drug Interactions in Polypharmacy: A Case Study of Patients with Heart Failure Hospitalized at Tangerang District Hospital - Sondang Khairani; Reise Reise Manninda Manninda; Lusiana Ariani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Heart failure is a condition in which the heart is unable to pump enough blood to meet the body's metabolic needs. It is a clinical syndrome with signs and symptoms caused by abnormalities in the structure and/or function of the heart. Heart failure occurs when the heart can't pump enough blood to meet the body's needs. It is caused by problems with the structure or function of the heart. This can lead to polypharmacy, where several medications are often taken by patients with heart failure to manage their condition. This study aims to identify patient characteristics, treatment accuracy based on Indonesian Heart Association (PERKI) 2023 guidelines, and the relationship between drug interactions and polypharmacy in adult patients diagnosed with heart failure with or without comorbidities at Tangerang Regency Hospital in 2023. The research was conducted descriptively using a cross-sectional study design. A total of 78 samples specimens met the inclusion criteria, with a male majority of 37 (52.86%) patients. The most common age group was 56-65 years old with 25 (35.71%) patients. The most common length of stay was 1-5 days with 48 (68.57%) patients. Evaluation of the treatment accuracy showed that the appropriate drug class was achieved in 78 (100%) patients, the appropriate dose in 55 (70.51%) patients and the appropriate frequency in 45 (57.69%) patients. Statistical tests showed a correlation between polypharmacy and drug-drug interactions with p-value 0.05. Accordingly, it is important to enhance monitoring and assessment of drug interactions in heart failure patients to optimize treatment management and prevent the risk of complications